Analisis Kemampuan Pemahaman Membaca Anak pada Proses Pembelajaran Bahasa Indonesia Materi Narasi Anak Kelas 4 SD Negeri 136 Palembang - Nurmala, Nurmala; Wardiah, Dessy; Kuswidyanarko, Arif (ANTHOR: Education and Learning Journal, 2022)
This study was to analyze or describe students' reading comprehension abilities in Indonesian language learning narrative material, describing the obstacles experienced by students in reading comprehension skills. This type of research is descriptive qualitative, data collection in this study is in the form of observation, interviews, and documentation. The data that has been collected can be processed through data validity and data reliability. The subjects in this study were 4A class students at SD Negeri 136 Palembang, totaling 24 students and the object was the students' comprehension ability in reading narrative material. The results of this study can show that students' reading comprehension abilities can be seen from the results of observations based on 5 categories, namely very capable categories, capable categories, quite capable categories, less able categories, incapable categories, and based on interviews students and teachers are already able to read well only, Of course, several students were not fluent in reading comprehension, consisting of 5 out of 24 students who experienceddifficulties in conveying reading comprehension due to factors in the school environment and family environment, then there were 3 students who had reading comprehension skills in the very capable category in reading comprehension. Based on these data, the ability to read comprehension of students' narrative material for grade 4 SD Negeri 136 Palembang is included in the capable category.